FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A.; Hellmer, Hartmut H.; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten; Hellmer, Hartmut H.; 1 Alfred‐Wegener‐Institute Helmholtz Center for Polar and Marine Research Bremerhaven Germany; Hattermann, Tore; 2 Norwegian Polar Institute Tromsø Norway; et al. (Journal of Geophysical Research: Oceans, 2021)
The Filchner‐Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near‐freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW‐sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer‐based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two‐year travel time, and the other located in the central Filchner Trough following a ∼six year‐long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW‐derived ISW (Ronne‐mode) or more locally derived Berkner‐HSSW (Berkner‐mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW‐cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne‐ISW preconditions Berkner‐HSSW production. The negligible density difference between Berkner‐ and Ronne‐mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW. Plain Language Summary: We visited the largest floating Antarctic ice shelf in the southern Weddell Sea in 2018 with an icebreaker expedition, and measured ocean temperature, salinity, meltwater content, and other parameters in front of the FRIS. We found that the ocean conditions were still dominated by the very cold ...